Non-Litigation Process Land Dispute Settlement For Legal Certainty - Teddy Chandra (Faculty of Law, Universitas Muslim Indonesia, Indonesia, 2019)
The purpose of this study is to try to make the legal instruments for land use hold land disputes over land disputes. The research method used in research responsibilities is normative juridical. The results of this study suggest that land disputes that are formed are multi-dimensional and complex covering legal, economic, political, and social culture, national defense needs. Land administration is very important to reduce land disputes by following the land suitability regulations with article 19 paragraph (2) letter c of the UUPA Land certificates form public administration products, if disputes occur in the future, land dispute resolution and non-litigation land dispute resolution can be resolved. The part of the government that actively participates in the community helps to make an important contribution to public administration in Indonesia with land disputes and non-litigation process. This model of law enforcement seeks to realize legal certainty in order to create a sense of security, peace and harmony, the impact of order will encourage people to try and work well as an effort to improve the quality of their lives. This article finally looks at the development of law by means of harmonizing values ​​to overcome the problem solving that does not exist, which is damaged or wrong, which is still lacking, congestion, and deterioration or a deterioration in circumstances. Win-win solutions are still strong enough and efficient to empower legal energy to resolve disputes in order to realize legal certainty and maintain social order in a culture.